LIFE EXTENSION TECHNIQUE FOR WELDED STRUCTURE USING HFMI/PIT: A REVIEW ON PAST AND CURRENT RESEARCHES WITH APPLICATIONS - Y. H. P. Manurung; M. A. Mohamed; D. Andud; A. Z. Abidin; S. Saidin; K. Kasim; D. P. Ishak (Universitas Mercu Buana, 2016)
In this paper, High Frequency Mechanical Impact (HFMI) using Pneumatic Impact Treatment (PIT) which can be applied for new or aging welded structure towards asset integrity will be discussed. The technology HFMI/PIT which falls under post weld treatment process is primarily aimed to enhance fatigue life and to strengthen welded joint. At first, the basic principle on fatigue of welded structure based on the IIW Recommendation will be briefly described. Further, various investigations conducted by prominent research universities or institutions and various industrial applications in European countries will be reviewed and discussed. Lastly, the current research on application of HFMI/PIT carried out under Advanced Manufacturing Technology Excellence Centre (AMTEx) at Faculty of Mechanical Engineering UiTM Shah Alam will be presented. As conclusion, it is stated that HFMI/PIT can be applied for extending the structural life and also for design optimization.